24+-2a+3=7a

Simple and best practice solution for 24+-2a+3=7a equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 24+-2a+3=7a equation:


Simplifying
24 + -2a + 3 = 7a

Reorder the terms:
24 + 3 + -2a = 7a

Combine like terms: 24 + 3 = 27
27 + -2a = 7a

Solving
27 + -2a = 7a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-7a' to each side of the equation.
27 + -2a + -7a = 7a + -7a

Combine like terms: -2a + -7a = -9a
27 + -9a = 7a + -7a

Combine like terms: 7a + -7a = 0
27 + -9a = 0

Add '-27' to each side of the equation.
27 + -27 + -9a = 0 + -27

Combine like terms: 27 + -27 = 0
0 + -9a = 0 + -27
-9a = 0 + -27

Combine like terms: 0 + -27 = -27
-9a = -27

Divide each side by '-9'.
a = 3

Simplifying
a = 3

See similar equations:

| 5(3-x)=-(1+x) | | x^2+x-18=2 | | -24=-4(k+3) | | 7h-7=17+4h | | y=x^2-7x+6 | | -2x+4=3(x-7) | | 21+9y-10=-277 | | 7x+9=8x+4 | | -7(x+9)=8x+42 | | 3(b+2)+2(x-5)=2 | | (2-z)(5z+3)=0 | | 5m+3=6m+7 | | 3(x+8)-8x=29 | | 3x^2=-6x-2 | | 9p+8q=100 | | 36x-4x+9+25x+7= | | (3x^2-6)=0 | | -(6(5xy+y^3)+5(9xy+7y^3))= | | -2a-11=7+7a | | 5x+5=-21-7x | | -3x^2-4x-5=0 | | 12p+6q=114 | | 2x*2x*2x+3x*3x*3x= | | 6a+2b=20 | | 160x-.8x^2=0 | | 200.00m+(-5600.00)=-2800.00 | | -5(x+5)=-15 | | 6p+4q=56 | | 3+2x=2(2+2x) | | 6x+-9=33 | | 200.00m+(-5600.00)=0.00 | | 3x-2(x+4)=15 |

Equations solver categories